Ethmoidal meningoencephalocele and cerebrospinal fluid leak after septoplasty: a rare complication - İmre, Abdulkadir; Pınar, Ercan; Ata Ece, Ahmet (ENT Updates, 2017)
A 24-year-old man referred to our clinic with complaint of intermittent right-sided watery rhinorrhea. Patient underwent nasal septoplasty one year ago and rhinorrhea occurred two weeks after the surgery. Rhinorrhea was ignored and then patient developed meningitis two months after the surgery. Subsequently, meningoencephalocele formation developed. In this case report, we present a case of meningoencephalocele associated with cerebrospinal fluid leak diagnosed one year after the septoplasty. Septoplasty is usually regarded as a relatively safe operation. However, forceful maneuvers to perpendicular lamina of the ethmoid bone may cause breakdown of the skull base structures, particularly the horizontal lamella of the cribriform plate. When this occur, immediate management is necessary to prevent intracranial complications including meningitis, intracranial abscess, and pneumocephalus. Delay in the diagnosis of such injury may cause erosion of the bone and gradual herniation of the intracranial contents through the skull base defect.